Adjusting Al location in the framework of ITH zeolites for catalytic conversion of methanol to olefins - Fan, Kai; Wu, Qinming; Liu, Shuo; Kong, Haiyu; Wang, Sen; Kunkes, Eduard; Baerdemaeker, Trees De; Parvulescu, Andrei-Nicolae; Bottke, Nils; Yokoi, Toshiyuki; Vos, Dirk E. De; Meng, Xiangju; et al. (Chinese journal of catalysis, 2024)
Adjusting location and distribution of Al sites in the zeolite framework is critical for catalysis, and typical strategies include using zeolites as starting Al source. However, this approach is still challenging for aluminosilicate ITH zeolite. Herein, the distribution of Al species in the framework of ITH was efficiently regulated by implementing LTA zeolite as the aluminum source added in the starting gels (LTA-ITH). The obtained LTA-ITH zeolites have similar nanosheet morphology, textual parameters, and acidic properties to those of conventional ITH synthesized from boehmite (C-ITH), while the results of 27Al MAS NMR spectra and 1-hexene cracking indicate that they have a different Al distribution. The use of LTA zeolite in starting gel is favorable for the formation of more Al species in sinusoidal and straight channels, compared with the C-ITH. Catalytic tests in the conversion of methanol to light olefin showed that LTA-ITH exhibited enhanced catalyst lifetime and propene selectivity compared with the C-ITH, which is reasonably attributed to the different locations of Al species in their respective ITH frameworks. [Display omitted]